Interactions between antiepileptic drugs and herbal medicines - Cecilie Johannessen Landmark (Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas, 2008)
As a therapeutic class, antiepileptic drugs (AEDs) have a high propensity to interact and many interactions with concomitant medicationshave been described. Increasingly, herbal medicines are often used by patients with epilepsy and the risk that these may interact with theirAED medication is now being realised. The purpose of this review is to highlight the interactions that have been reported between AEDs andherbal medicines. Overall, the published data are sparse and comprise of both pharmacodynamic (preclinical only) and pharmacokinetic(preclinical and clinical) interactions. Pharmacodynamic interactions between diazepam and the Chinese herb Saiboku-to and with Ginkgobiloba, and between phenytoin, valproate and gabapentin and Centella asiatica have been described. Pre-clinical studies suggest that theJapanese herbs Sho-seiryu-to and Sho-saiko-to, the herbal infusion preparation from Cassia auriculata, the traditional Chinese herbalmedicine Paeoniae Radix and the herb Mentat can affect the pharmacokinetics of carbamazepine by various mechanisms. Pharmacokineticinteractions have also been reported with phenytoin (Paenoniae Radix, Ayurvedic syrup shankhapushpi), phenobarbital (Ginkgo biloba) anddiazepam (the Chinese herbs Angelica dahurica and Salvia miltiorrhiza Bge). Clinical studies have reported a reduction in serumcarbamazepine concentrations when co-administered with the traditional Chinese herb Free and Easy Wanderer Plus and also a reduction inserum midazolam concentrations by Echinacea and by St Johns Wort. The mechanism of these interactions is considered to be induction ofhepatic metabolism. In contrast, piperine elevates serum phenytoin concentrations, possibly be enhancing the gastrointestinal absorption ofphenytoin. More research and information are required in order to clarify the propensity of AEDs and herbal medicine to interact andtherefore potentially compromise the therapeutics of AEDs.